Primary Pure Squamous Cell Carcinoma of Gallbladder Presenting as Acute Cholecystitis - Hosseinzadeh, Massood (Shiraz University of Medical Sciences, 2012)
Squamous cell carcinoma of the gallbladder is rare and constitutes only 0.5-3% of all malignancies of this organ. Most of the reported cases have had a component of adenocarcinoma. We report a 70-year-old man who presented with acute onset right upper quadrant pain. He operated on based on a presumptive diagnosis of acute cholecystitis according to clinical and ultrasonographic findings. Histopathological examination of the infiltrating mass of the gallbladder revealed well differentiated keratinized squamous cell carcinoma invading full wall thickness. Thorough evaluations revealed no other primary site for the tumor. Pure primary squamous cell carcinoma of the gallbladder is rarely reported. Clinicians and pathologists must be aware of its vague clinical presentations.